Pengaruh Intensitas Penggunaan Media Sosial Terhadap Akhlak Siswa: (Penelitian di kelas XI SMAN 1 Garut) - Rudiansyah, Taopiq; Masripah, Masripah; Usman, Asep Tutun; Nazib, Fiqra Muhamad (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Social media users have a great influence on their users, because the content on social media is very diverse, which is a challenge in itself, especially for students to always sort and choose the content they consume. This research uses quantitative methods. This study aims to examine the effect of the intensity of social media use on students' morals in class XI of SMAN 1 Garut. Data analysis shows that the level of social media use of students in class XI of SMAN 1 Garut is categorized as low, with a percentage of 69%, and their morals are also in the moderate category, with a percentage result of 66%. This study used a random sampling technique; the sample taken was 96 students with a significance level of 10%. After a simple linear regression analysis, a coefficient value of 0.228 was obtained, which means that the variable intensity of social media use (X) contributed 22.8% to student morale. The ANOVA test results show the F-count value of 27.811 with a significance value (sig) of 0.000 < 1.10. Thus, the results of this effect test show that the intensity of social media use has a positive effect on the morals of students in class XI of SMAN 1 Garut.   Keywords: Morals, Social Media, Students, Technology